The Effect of Glycerol Concentration on The Characteristics of Edible Film of Kimpul Starch (Xanthosoma sagittifolium): Kimpul starch (Xanthosoma sagittifolium) based edible film - Surhaini, Surhaini; Indriyani, Indriyani; Affandi, Affandi (Jurnal Bio-Geo Material Dan Energi, 2023)
Edible film is a thin layer that has the function of packaging or coating food that can be consumed directly with the packaged product. Edible film made from starch has the disadvantage that it is fragile and easy to use. The aim of this research is to determine the effect of glycerol concentration on the characteristics of edible film from kimpul tuber starch. The experiment was carried out using a completely randomized design (CRD), with 4 treatments with glycerol concentrations of 0.5%, 1.0%, 1.5% and 2.0%, each treatment was repeated 4 times. The results showed that the solubility, thickness, wvtr, and elongation values increased with increasing glycerol concentration used. A glycerol concentration of 2.0% produces the highest solubility value of 58.33%, thickness of 0.174mm, wvtr 33.38g/m2.hour, and elongation is found at a glycerol concentration of 1.0% with a value of 21.397%. However, on the contrary, the transparency, compressive strength, and tensile strength of edible film decrease with increasing glycerol concentration. Glycerol concentration has a significant effect on the values of solubility, thickness, transparency, compressive strength, tensile strength and elongation, but does not have a significant effect on the value of the water vapor transmission rate (WVTR). A glycerol concentration of 1% produces the best edible film with a solubility value of 38.33%, thickness of 0.125mm, transparency of 18.656%/mm, WVTR of 28.25g/m2.hour, compressive strength of 103.56N/m2, Tensile Strength of 2.9428MPa, and Elongation 21.397%.